The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5007/2175-7925.2012v25n3p39
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo de nutrientes e resposta da alface à adubação fosfatada

Abstract: RESUMO O objetivo deste trabalho foi determinar a curva de acúmulo de nutrientes pela planta de alface destinada à produção de sementes. O experimento foi conduzido na Fazenda Experimental São Manuel, pertencente à Faculdade de Ciências Agronômicas da Universidade Estadual Paulista, no período de 25/09/03 a 19/02/04. O delineamento experimental utilizado foi em blocos ao acaso com cinco repetições e seis tratamentos (épocas de coleta das plantas: 0, 20, 34, 49, 69 e 112 dias após o transplante (DAT)). Foi util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
10
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 10 publications
8
10
1
1
Order By: Relevance
“…KANO et al (2012) found similar results with conventional soil system with Ca concentrations ranging from Effect of different substrates in aquaponic lettuce production associated with intensive tilapia farming ALMEIDA et al (2011) reported lower Ca concentrations in hydroponics compared to this work, with concentrations ranging from 3.6 to 12,1g kg -1 .…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…KANO et al (2012) found similar results with conventional soil system with Ca concentrations ranging from Effect of different substrates in aquaponic lettuce production associated with intensive tilapia farming ALMEIDA et al (2011) reported lower Ca concentrations in hydroponics compared to this work, with concentrations ranging from 3.6 to 12,1g kg -1 .…”
Section: Resultssupporting
confidence: 73%
“…However, they showed no visible deficiency symptoms. KANO et al (2012) found similar results, in conventional soil system, with Mg concentrations between 3.1 to 3.6 g kg -1 , below the recommended by RAIJ et al (1996). In hydroponic culture, ALMEIDA et al (2011) also found concentrations below the appropriate, with Mg concentrations between 0.7 and 5.5 g kg -1 .…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations